Meningkatkan Kemampuan Penalaran Matematis Mahasiswa pada Materi Himpunan Melalui Penerapan Model Pembelajaran Project Based Learning - Feriyanto, Feriyanto; Ulil Nurul Imanah (Tematik : Jurnal Konten Pendidikan Matematika, 2024)
Students are still not able to solve contextual questions that require the ability to reason well. Project Based Learning is a learning model that requires teachers and/or students to develop guiding questions (a guiding question). This research is a Classroom Action Research (CAR) with lecturers and first-semester students as subjects of mathematics education study programs at Majapahit Islamic University Academic Year 2022/2023. Data collection techniques were in the form of direct observation of learning activities, interviews with lecturers and students, tests of students' mathematical reasoning abilities, and documentation. Data analysis techniques in this study include 1) analysis of observational data, namely the activities of teachers and students during the process of learning mathematics; 2) data analysis of students' mathematical reasoning abilities test by paying attention to the mathematical reasoning scoring rubric. While the results of this study are that the application of the project-based learning (Pjbl) learning model has succeeded in increasing students' mathematical reasoning abilities, this is due to an increase in the average results of observations of the implementation of learning by lecturers and students as well as mathematical reasoning abilities in set material with project-based learning models from cycle I to cycle II